An examination of sociodemographic and clinical factors influencing help-seeking attitudes and behaviors among adolescents with mental health problems - Cavelti, Marialuisa; Ruppen, Noemi Anne; Sele, Silvano; Moessner, Markus; Bauer, Stephanie; Becker, Katja; Krämer, Jennifer; Eschenbeck, Heike; Rummel-Kluge, Christine; Thomasius, Rainer; Diestelkamp, Silke; Gillé, Vera; et al. (European child & adolescent psychiatry, 2025)
This study investigated sociodemographic and clinical factors influencing help-seeking attitudes and behavior among adolescents with mental health problems. As part of the ProHEAD (“Promoting Help-seeking using E-technology for ADolescents”) consortium a school-based, online assessment of sociodemographic information, psychopathology, risk-taking and self-harming behavior, help-seeking attitudes and behavior, and barriers to help-seeking was conducted in adolescents aged ≥ 12 years recruited from randomly selected schools in five regions of Germany. Linear regression analyses with the LMG formula were performed to explore predictors of help-seeking attitudes and behavior and assess their relative importance. Nine thousand five hundred and nine participants (95.5%) completed the online assessment (mean age: 15.1 years, 58.6% female). In total, 1606 participants (16.9%) showed relevant mental health problems (e.g., depressive and eating disorder symptoms, alcohol problems, and thoughts of self-harming behavior). Among them, 895 (55.7%) reported having sought help (lifetime), with higher rates for informal (n = 842, 52.4%) compared to professional (n = 380, 23.7%) sources. High help-seeking propensity emerged as the most important factor contributing to professional help-seeking, followed by elevated levels of psychopathology and perceived barriers, with sociodemographic factors being less impactful. Psychopathological severity also outweighed sociodemographic factors in predicting negative help-seeking attitudes. These findings indicate that attitudes towards seeking professional help, perceived barriers, and psychopathology severity critically influence limited adolescent help-seeking behavior. This emphasizes the need for initiatives that promote help-seeking, reduce negative attitudes, and address structural barriers in adolescent mental health care.
Online veröffentlicht: 27. August 2024
Online veröffentlicht: 27. August 2024
Gesehen am 24.10.2024